2020
DOI: 10.1371/journal.pone.0239559
|View full text |Cite
|
Sign up to set email alerts
|

‘You’re not just a medical professional’: Exploring paramedic experiences of overdose response within Vancouver’s downtown eastside

Abstract: Background Overdose response has become an increasingly relevant component of paramedic practice, particularly in light of increased opioid overdose globally. Previous studies have noted gaps in our understanding regarding the unique challenges which paramedics face during this form of pre-hospital emergency care. The aim of this study is to explore and describe the ways in which paramedics experience overdose response, specifically within a community markedly affected by the overdose crisis. Methods Ten parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…Calling emergency health services (EHS) (i.e., 911) in the case of overdose is therefore a critical and potentially life-saving intervention [10]. Furthermore, EHS provide a critical response in cases of complications (e.g., overdoses complicated by benzodiazepines in the illicit supply), which are increasingly common in BC [5,11]. Nevertheless, prior studies identified that concerns about police presence and arrests represent a significant barrier to calling 911 in the event of an overdose [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Calling emergency health services (EHS) (i.e., 911) in the case of overdose is therefore a critical and potentially life-saving intervention [10]. Furthermore, EHS provide a critical response in cases of complications (e.g., overdoses complicated by benzodiazepines in the illicit supply), which are increasingly common in BC [5,11]. Nevertheless, prior studies identified that concerns about police presence and arrests represent a significant barrier to calling 911 in the event of an overdose [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…14 By empowering paramedics with the tools to provide holistic care, we can foster their resilience, purpose and empathy towards people who use drugs, leading to improved wellness, job satisfaction and patient outcomes. 71 The paramedic role exerts a significant influence on a patient's healthcare journey, and it is crucial that we direct research attention to this highly understudied area. 90 Ultimately, holistic models of care can enhance the relationship between paramedics and people who use drugs, driving meaningful progress towards reducing harm and improving health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…68 Five major themes identified by a study of paramedic attitudes in Vancouver, BC, included: connecting with patients' lived experiences; occupying roles as clinicians and patient advocates; navigating on-scene hazards; difficulties with transitions of care; and emotional burden of the drug poisoning crisis. 71 The core category discovered from this study was one's capacity to help, identified by a limited capacity to follow up on patients, to emotionally process stressful encounters and to address the needs of a patient who experiences a drug poisoning event. Despite paramedics feeling highly confident in their role as clinical care providers, their capacity to treat the underlying drug use is described as much more limited.…”
Section: Empathy and Attitudes Of Paramedics And Paramedic Studentsmentioning
confidence: 99%
“…Five major themes identified by a study of paramedic attitudes in Vancouver, BC included: connecting with patients' lived experiences; occupying roles as clinicians and patient advocates; navigating on-scene hazards; difficulties with transitions of care; and emotional burden of the toxic drug crisis (61). The core category discovered from this study was one's capacity to help, identified by a limited capacity to follow up on patients, to emotionally process stressful encounters, and to address the needs of a patient who experiences a drug poisoning event.…”
Section: Empathy and Attitudesmentioning
confidence: 99%